Flexible microblanking of amorphous alloys under laser dynamic loading. (August 2020) - Cui, Jiankun; Liu, Huixia; Ma, Youjuan; Li, Maowen; Gong, Jinxi; Zhang, Yunfeng; Wang, Xiao
Abstract: In order to overcome the poor plasticity of amorphous alloy at room temperature, this paper uses soft film as a micro punch to punch out the gear hole on the amorphous alloy with a thickness of 30 μm under laser loading. This paper mainly studies the fracture morphology and fracture mode of the workpiece; the process window of laser energy and the thickness of soft punch; the mechanical properties and surface quality of the workpiece. The fracture surface of the workpiece is mainly composed of smooth zone and veined zone. There are two modes of brittle fracture and plastic fracture, and from the addendum to the dedendum of gear, the material gradually transitions from brittle fracture to plastic fracture. When the laser energy and the soft punch thickness are 1520 mJ and 200 μm respectively, the workpiece can achieve a balanced forming quality. With the laser energy increases, the softening effect caused by adiabatic temperature rise and free volume exceeds the hardening effect caused by compressive stress, resulting in nanohardness increasing first and then decreasing. And the change trend of the surface roughness is the same.